DIPEPTIDYL PEPTIDASE IV INHIBITORY ACTIVITY OF PROTEIN HYDROLYZATES FROM AMARANTHUS HYPOCHONDRIACUS L. GRAIN AND THEIR INFLUENCE ON POSTPRANDIAL GLYCEMIA IN STREPTOZOTOCIN-INDUCED DIABETIC MICE. - Soriano-Santos, Jorge; Reyes-Bautista, Raúl; Guerrero-Legarreta, Isabel; Ponce-Alquicira, Edith; Escalona-BuendÃa, Héctor Bernardo; Almanza-Pérez, Julio César; DÃaz-GodÃnez, Gerardo; Román-Ramos, Rubén (African Journal of Traditional, Complementary and Alternative Medicines, 2014)
Background: Type 2 diabetes is a chronic metabolic disorder. Recently, dipeptidyl peptidase IV (DPP-IV) inhibitors that protect incretin hormones from being cleaved by DPP-IV have been used as drugs to control glycemia. This study examined the potential hypoglycemic effect of amaranth grain storage protein hydrolyzates to control postprandial glycemia in streptozotocin (STZ)-induced diabetic mice as a model system of diabetes, and their inhibition mode on the enzyme. Material and Methods: Amaranth grain proteins were isolated and hydrolyzed and fractionated by gel filtration. The DPP-IV inhibitory activity of hydrolyzates as well as their kinetic parameters were assessed. Selected hydrolyzates (300 mg/kg body weight) were administered in a single administration-study (SAS) or in the same concentration during a four-week chronic daily dosing study (FWCDDS) in order to observe the effect on postprandial glycemia of diabetic mice. Results: Albumin 1, Globulin and Glutelin hydrolyzates (GluH) competitively inhibited DPP-IV in vitro (Ki= 0.11-5.61 mg/mL). GluH called Glu.III (IC50= 0.12±0.01 mg/mL) considerably inhibited DPP-IV activity. GluH identified as GluH24 improved glucose tolerance significantly (p<0.05), with remarkable increments in plasma insulin in SAS and FWCDDS (1.25 and 2.25 mg/mL, respectively). This effect could be compared to the one obtained from the mice group that was administered Sitagliptin (580 mg/kg body weight) as positive control (p<0.05). Conclusion: Amaranth Glutelin hydrolyzates yielded the highest enzyme inhibitory activity reported not only in vitro, but also in the STZ-induced diabetic mice in order to control postprandial glycemia.